Pemanfaatan Etnomatematik Melalui Permainan Engklek Sebagai Sumber Belajar - Ema Butsi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2015)
The influence of modernity has mostly impact on lost of local cultural values, then the understanding mathematical concept at elementary student is decreasing, because of means limited, teacher who is lazy to write the ideas in lesson plan, and teacher’s job which is hard. The aim of this public service is to socialize etnomatematics through traditional game engklek modified its rule as inovation of mathematical learning stratgey. The location of public service conducted in SD/MI, Telukan subdistrict followed by 22 teacher delegation. The procedure of program by giving guidelines of etnomathematics definition, engklek game system, etnomathematics based engklek implementation, and ended by evaluation, namely teacher simulation using theme of curriculum 2013.